Dopamine Surface Modification of Trititanate Nanotubes: Proposed In‐Situ Structure Models. Issue 17 (22nd March 2016) - Liu, Ruochen; Fu, Xuejian; Wang, Congyi; Dawson, Graham
Abstract: Two models for self‐assembled dopamine on the surface of trititanate nanotubes are proposed: individual monomer units linked by π–π stacking of the aromatic regions and mono‐attached units interacting through hydrogen bonds. This was investigated with solid state NMR spectroscopy studies and powder X‐ray diffraction. Abstract : Double bind : Two models for self‐assembled dopamine on the surface of trititanate nanotubes are proposed: individual trimer units linked by π–π stacking of the aromatic regions and mono‐attached units interacting through hydrogen bonds. This was investigated by solid state NMR spectroscopy studies and powder X‐ray diffraction.